Subjective Rank of the Competition as a Factor Differentiating Between the Affective States of Swimmers and Their Sport Performance - Samełko, Aleksandra; Guszkowska, Monika; Kuk, Anna (Frontiers in Psychology, 2020)
Purpose. The aim of the study was to establish the differences in affective states of swimmers depending on the subjective rank of the competition and the relationship between affective states and performance in sports competitions of low, medium and high subjectively perceived rank. Methods. The respondents (n = 31) aged from 15 to 23 years (18.1 ± 2.397) were studied using the psychological questionnaires Perceived Stress Scale (PSS-10), Profile of Mood State (POMS), and Positive and Negative Affect Schedule (PANAS) during sports events. 362 measurements using POMS and 232 measurements using PANAS before the starts were collected. The significance of intergroup differences was determined using the Kruskal-Wallis test. A stepwise regression analysis was used to determine the emotional predictors of sports results. Results. Subjective rank of sports competition differentiated significantly anger (chi2 = 6.826; p = .033), confusion (chi2 = 11.345; p = .003), depression (chi2 = 10.2; p = .006), fatigue (chi2 = 49.394; p ≤ .001), vigour (chi2 = 11.345; p ≤ .001), positive emotions (chi2 = 51.233; p ≤ .001), and negative emotions (chi2 = 11.552; p = .003). Regression analysis showed the influence of mood states and positive emotions on the sports result. Conclusions. The swimmers' affective state changed depending on the subjective rank of the competition. Depression and positive emotional state made it possible to predict the result in medium- and high-rank competition.